Molecular epidemiology of a familial cluster of SARS-CoV-2 infection during lockdown period in Sant Kabir Nagar, Uttar Pradesh, India. (25th August 2021) - Zaman, Kamran; Shankar, Prem; Yadav, Pragya D.; Nyayanit, Dimpal A.; Behera, Sthita Pragnya; Bhardwaj, Pooja; Shete, Anita; Majumdar, Triparna; Yadav, Rajaram; Patil, Savita; Deval, Hirawati; Dwivedi, Gaurav Raj; et al.
Abstract: We report a familial cluster of 24 individuals infected with severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). The index case had a travel history and spent 24 days in the house before being tested and was asymptomatic. Physical overcrowding in the house provided a favourable environment for intra-cluster infection transmission. Restriction of movement of family members due to countrywide lockdown limited the spread in community. Among the infected, only four individuals developed symptoms. The complete genome sequences of SARS-CoV-2 was retrieved using next-generation sequencing from eight clinical samples which demonstrated a 99.99% similarity with reference to Wuhan strain and the phylogenetic analysis demonstrated a distinct cluster, lying in the B.6.6 pangolin lineage.